Barrier Jump Training to Leg Muscle Explosive Power (Department of Physical Education, Sport, Health and Recreation, 2020)
The objective of this research is to determine the impact or effect resulting from the provision of barrier jump training on the explosive power of leg muscles of male volleyball extracurricular participants at Junior high school Sila Candra Batubulan. This research is an experimental research with experimental research design randomize pre and post group design. This research was conducted for 6 weeks with a frequency of 4 times a week. The number of samples in this study were 30 people who were divided into 2 groups. Based on the above discussion, it can be concluded that barrier jump training increases the explosive power of the leg muscles of male volleyball extracurricular participants at Junior high school Sila Candra Batubulanwith an average increase of 8.69 cm (20.69%) with a p value <0.05.